Effects of childhood trauma on mental health outcomes, suicide risk factors and stress appraisals in adulthood - Leizhi Wang; Chris Keyworth; Daryl B. O'Connor (PLoS ONE, 2025)
Background Childhood trauma has been identified as a significant risk factor for adverse mental health outcomes and increased suicide risk. However, the mechanisms by which stress-related variables, such as stress appraisal, influence this pathway remain unclear. The current study sought to: (1) investigate whether childhood trauma was associated with mental health outcomes (depression, anxiety), suicide risk factors (defeat, entrapment), and stress related outcomes (stress appraisal, perceived stress) in adulthood and (2) determine whether stress appraisal and perceived stress mediate the effects of childhood trauma on mental health outcomes and suicide risk factors. Method 273 participants were recruited to an online prospective study that consisted of two sessions with a one-week interval. In session 1, the childhood trauma questionnaire was completed. In session 2, participants completed measures assessing the level of depression, anxiety, defeat, entrapment, stress appraisal and perceived stress over the preceding week. Results Analyses found that childhood trauma was significantly associated with higher scores on depression, anxiety, defeat, entrapment, stress appraisal and perceived stress. Childhood trauma also had indirect effects on depression, anxiety, defeat, and entrapment through stress appraisal and perceived stress. Conclusion These findings underscore the enduring impact of childhood trauma on mental health outcomes and suicide risk in adulthood, mediated through its influence on stress appraisals and perceptions of stress encountered in daily life. These underlying mechanisms are critical for informing the development of future interventions.